The Link Between Middle School Mathematics Course Placement and Achievement. Issue 5 (12th May 2014) - Domina, Thurston
<x xml:space="preserve">Abstract</x> The proportion of eighth graders in United States public schools enrolled in algebra or a more advanced mathematics course doubled between 1990 and 2011. This article uses Early Childhood Longitudinal Study's Kindergarten Cohort data to consider the selection process into advanced middle school mathematics courses and estimate the effects of advanced courses on students' mathematics achievement (n = 6, 425; mean age at eighth grade = 13.7). Eighth‐grade algebra and geometry course placements are academically selective, but considerable between‐school variation exists in students' odds of taking these advanced courses. While analyses indicate that advanced middle school mathematics courses boost student achievement, these effects are most pronounced in content areas closely related to class content and may be contingent on student academic readiness.